Exploring thought leadership via leadership IQ of the Singapore working population. - Kuah, Yiru. (2008)
In this fourth ARP on Thought Leadership, we attempt to consolidate and review past ARPs and literature on this topic to identify trends and discrepancies, identify characteristics and attributes belonging to thought leaders in the working population, and to set the direction for future study on this subject.